The Introduction of Self Contained Self Rescuers into the South African Mining Industry (The Australasian Institute of Mining and Metallurgy, 1988)
The Government Mining Engineer of South Africa has decided to legislate that Self Contained Self Rescuers (S.C.S.R.) become a mandatory piece of equipment for all those persons proceeding underground. It is envisaged that: * employees in underground coal mines will be fully equipped with S.C.S.R.s during 1988; * those persons employed in gold mines during 1988/89; and * personnel in all other mines by the end of 1990. It is the intention of this paper to discuss the introduction of these auxiliary life support systems, and to give an update on current market developments.